To retouch or not to retouch? – Reflections on the aesthetic completion of wall paintings - Isabelle Brajer (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Decision-making regarding the aesthetic treatment of wall paintings can be a difficult and complex process due to the multifaceted issues that influence the choices. In addition, local views and national value assignations make it difficult to apply general guidelines for retouching. This paper describes general theoretical concerns presented on the backdrop of specific examples, illustrating a wide range of aesthetic solutions for wall paintings.